Принципи побудови компресійних магнітно-напівпровідникових пристроїв для імпульсних технологій та лазерів - Волков, І.В.; Зозульов, В.І.; Шолох, Д.О. (Технічна електродинаміка, 2011)
The results of major studies aspects of the both compression magnetic semiconductor generato rs and convertors construction is considered (the main results of “Dose-2” project). Scientific and technical basis for compression devices development was showed. Practical application of compression generators, converters and their details was described.